Poverty and Income Effects on Southeast Sulawesi Local Tax Revenue - Rizal; Khelana Ramadhan; Abdullah Igo; Murniati; Inggah Pratiwi; Fitri Ramadhani (Economics Development Analysis Journal, 2025)
This study uses a quantitative descriptive statistical approach to examine the impact of poverty levels and per capita income on regional tax revenues in Southeast Sulawesi. Utilizing secondary data from 2012 to 2021, the analysis employs a multiple linear regression model to evaluate the relationships between the variables. The findings reveal that poverty levels do not significantly affect regional tax revenues, whereas per capita income exerts a positive and substantial influence, highlighting its critical role in enhancing fiscal performance. The study underscores the importance of per capita income in boosting regional tax revenue. It recommends that the Southeast Sulawesi government prioritize economic empowerment initiatives, such as vocational training, micro-enterprise financing, and expanded market access, to increase community income and encourage greater participation in the taxation system. Further research should investigate other factors influencing tax revenues, including education levels, poverty dynamics, and regional economic structures. A broader analysis of these variables can provide policymakers with a more comprehensive framework for optimizing regional tax revenue and addressing socioeconomic disparities in the region.